1994
DOI: 10.1021/ac00094a034
|View full text |Cite
|
Sign up to set email alerts
|

Improved Peroxyoxalate Chemiluminescence-Based Determinations by Use of Continuous Reagent Addition To Remove Background Emission

Abstract: The continuous addition of reagent technique was used as an effective means for suppressing background emission in peroxyoxalate chemiluminescence reactions. For this purpose, the bis(2,4,6-trichlorophenyl) oxalate/hydrogen peroxide system and phenothiazine derivatives such as acepromazine, propiopromazine, thioridazine, promazine, trimeprazine, methotrimeprazine, and chlorpromazine were chosen. The influence of environmental factors such as pH, water content, reagent concentration, and addition rate on the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…HAuCl 4 was purchased from Shanghai Chemical Reagent Company (Shanghai, China). Solutions of 1.0 mol/L H 2 O 2 , 0.1 mol/L sodium citrate (C 6 H 5 Na 3 O 7 ) and 1.0% HAuCl 4 were prepared by directly dissolving the solute in pure water. 0.01 mol/L TCPO was prepared in acetonitrile.…”
Section: Reagentsmentioning
confidence: 99%
“…HAuCl 4 was purchased from Shanghai Chemical Reagent Company (Shanghai, China). Solutions of 1.0 mol/L H 2 O 2 , 0.1 mol/L sodium citrate (C 6 H 5 Na 3 O 7 ) and 1.0% HAuCl 4 were prepared by directly dissolving the solute in pure water. 0.01 mol/L TCPO was prepared in acetonitrile.…”
Section: Reagentsmentioning
confidence: 99%
“…For example, Basavaiah et al [26] reported a DL of 27 ng/mL by UV spectrophotometry. When using the hydrogen peroxide-bis(2,4,6-trichlorphenyl)oxalate chemiluminescence system [7] and tris(2,2 -bipyridy)ruthenium(II)-based electrogenerated chemiluminescence system [10], 66.5 and 240 ng/mL of DL were reported; respectively. So, the high sensitivity of the proposed method allows the determination of chlorpromazine hydrochloride in biological fluids.…”
Section: Analysis Of Real Urine Samplesmentioning
confidence: 99%
“…CL reactions have been reported for the determination of chlorpromazine [7][8][9][10]. Over the past few years, increasing interest has been given to the use of the reversed micellar system in CL analysis [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The increasing use of promazine in medicine has prompted the development of several methods for its quantitative determination in bulk form and pharmaceutical preparations. For this purpose, a wide variety of analytical techniques were utilized including titrimetry [ 9 , 10 ], spectrophotometry [ 7 , 8 , 11 ], chemiluminescence [ 12 , 13 ], electrophoresis [ 14 , 15 ], conductimetry [ 16 ], polarography [ 17 ], and FIA [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%